THE EFFECT OF MOTIVATION TOWARDS MATHEMATICAL COMMUNICATION IN MATHEMATICS LEARNING WITH BRAIN-BASED LEARNING MODEL - Kiki Nia sania Effendi; Rina Marlina (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2021)
This research is motivated by the importance of students' learning motivation and the low of high school students’ mathematical communication skills in learning mathematics. The purpose of this study was to determine the effect of learning motivation on the high school students’ mathematical communication skills in learning mathematics with the Brain-Based Learning model. This research is mixed-method research with concurrent triangulation strategies. The population in this study were all class XI in SMA 1 Rengasdengklok on Kabupaten Karawang and the sample was one class. Data was collected by providing tests, observations, questionnaires, and interviews. The test used is a description test, while the motivation scale uses a Likert Scale. The data was analyzed by normality test and simple linear regression. The results of this study indicate that there is an influence of learning motivation on mathematical communication skills in the application of the Brain-Based Learning model with a percentage of 56.8%.